Albuminuria predicts worsening renal function after transcatheter aortic valve replacement. Issue 5 (May 2022) - Tobe, Akihiro; Tanaka, Akihito; Tokuda, Yoshiyuki; Fujii, Taro; Furusawa, Kenji; Ishii, Hideki; Usui, Akihiko; Murohara, Toyoaki
Highlights: The impact of preoperative albuminuria on clinical outcomes after transcatheter aortic valve replacement (TAVR) is unknown. Worsening renal function (WRF) after TAVR is reported to predict poor prognosis. This study showed preoperative albuminuria independently predicted WRF after TAVR. All-cause death and heart failure occurred frequently in patients with albuminuria. Albuminuria can be a useful predictor of poor clinical outcomes after TAVR. Abstract: Background: The impact of albuminuria on worsening renal function (WRF) and clinical outcomes after transcatheter aortic valve replacement (TAVR) is unknown. Methods: Overall, 142 patients who underwent TAVR for severe aortic stenosis were divided into two groups based on the preoperative urinary albumin-to-creatinine ratio (ACR): high (ACR ≥30 mg/g) and low (ACR <30 mg/g). The incidence of WRF (an absolute increase in serum creatinine level of ≥0.3 mg/dL or ≥1.5-fold from baseline or dialysis initiation) at 6 months after TAVR and the incidence of all-cause death and heart failure readmission during follow-up were investigated. Results: Half of the examined patients [n=71/142 (50.0%)] had a high ACR. Patients with a high ACR more frequently had WRF at 6 months than those with a low ACR (17.6% vs. 2.9%, p =0.004). Multivariate analysis showed a high ACR was independently associated with WRF (odds ratio, 7.76; 95% confidence interval, 1.62–37.30; p =0.01), whereas baseline estimated glomerular filtration rate <60 mL/min/1.73m² was not (odds ratio, 0.34; 95% confidence interval, 0.08–1.50; p =0.15). Patients with a high ACR had a higher risk of composite outcomes of all-cause death and heart failure readmission ( p =0.002). Conclusions: Preoperative albuminuria (ACR ≥30 mg/g) was independently associated with WRF at 6 months after TAVR. Furthermore, patients with an ACR ≥30 mg/g had higher risks of all-cause death and heart failure readmission than those with an ACR <30 mg/g. Graphical abstract: Image, graphical abstract